PERAN PEMUPUKAN POSFOR DALAM PERTUMBUHAN TANAMAN JAGUNG (Zea mays L.) DI TANAH REGOSOL DAN LATOSOL - FahmF, Arifin; Syamsudin, Syamsudin; Utami, Sri Nuryani H; Radjagukguk, Bostang (BERITA BIOLOGI, 2009)
Phosphorus (P) is an essential element for plants, deficiency and excess of P in soil will limit plant growth. It is required to applicate P fertilizer in appropriate dosage for promoting plant growth on the soil with different properties. The purpose of experiment was to study the respon of maize (Zea mays L.) for phosphorus fertilization on Regosol and Latosol soils. A glass house experiment was conducted to study maize response on P fertilizer application in Regosol and Latosol soils. The treatment 1was 0, 112, 336, 1008, 3024 and 9072 kg superfosfat ha . P fertilizer tend to increase the biomass of maize but exceed of P fertilizer reduced maize biomass. The optimum fertilization and vailability of P for plant affected by soil properties.